THE EFFECTIVENESS OF LEARNING MANAGEMENT APPLICATION IN FOUNDATION ENGINEERING BASED ON E-MODULES IN THE BUILDING ENGINEERING EDUCATION PROGRAM, STATE UNIVERSITY OF JAKARTA - Santoso Sri Handoyo; Rezi Berliana Yasinta; Diah Ayu Wukir; Husnaini; Nabila Rizqiani (LPPM Universitas Negeri Jakarta, 2025)
This study aims to evaluate the effectiveness of e-module-based learning in the Foundation Engineering I course. The research method employed is an experimental approach with two groups. The learning material consists of four learning activities (KB1, KB2, KB3, and KB4). The research instrument includes learning outcome tests conducted before (pre-test) and after (post-test) the learning process. The findings show that the experimental group experienced learning outcome improvements of 29.40% (KB1), 33.94% (KB2), 58.41% (KB3), and 24.51% (KB4). Meanwhile, the control group achieved increases of 25.74% (KB1), 31.67% (KB2), 51.80% (KB3), and 22.44% (KB4). The average learning outcome improvement in the experimental group was 36.49%, slightly higher than the control group at 32.93%, with a difference of 3.56%. However, statistical analysis revealed no significant difference between the two groups. This study indicates that e-modules are not yet fully effective in enhancing learning outcomes in the Foundation Engineering I course. The effectiveness of e-module-based learning is influenced by various factors, such as the e-module design, interactivity, and students’ readiness to utilize technology. Additionally, the complexity of Foundation Engineering I material necessitates intensive guidance from lecturers to support mathematical and conceptual understanding.